Prevalence of refractory hypertension in the United States from 1999 to 2014. Issue 9 (September 2019) - Buhnerkempe, Michael G.; Botchway, Albert; Prakash, Vivek; Al-Akchar, Mohammad; Nolasco Morales, Carlos E.; Calhoun, David A.; Flack, John M.
Abstract : Objectives: Refractory hypertension has been defined as uncontrolled blood pressure (at or above 140/90 mmHg) when on five or more classes of antihypertensive medication, inclusive of a diuretic. Because unbiased estimates of the prevalence of refractory hypertension in the United States are lacking, we aim to provide such estimates using data from the National Health and Nutrition Examination Surveys (NHANES). Methods: Refractory hypertension was assessed across multiple NHANES cycles using the aforementioned definition. Eight cycles of NHANES surveys (1999–2014) representing 41 552 patients are the subject of this study. Prevalence of refractory hypertension across these surveys was estimated in the drug-treated hypertensive population after adjusting for the complex survey design and standardizing for age. Results: Across all surveys, refractory hypertension prevalence was 0.6% [95% confidence interval (CI) (0.5, 0.7)] amongst drug-treated hypertensive adults; 6.2% [95% CI (5.1, 7.6)] of individuals with treatment-resistant hypertension actually had refractory hypertension. Although the prevalence of refractory hypertension ranged from 0.3% [95% CI (0.1, 1.0)] to 0.9% [95% CI (0.6, 1.2)] over the eight cycles considered, there was no significant trend in prevalence over time. Refractory hypertension prevalence amongst those prescribed five or more drugs was 34.5% [95% CI (27.9, 41.9)]. Refractory hypertension was associated with advancing age, lower household income, black race, and also chronic kidney disease, albuminuria, diabetes, prior stroke, and coronary heart disease. Conclusions: We provided the first nationally representative estimate of refractory hypertension prevalence in US adults.